Evaluasi Berpikir Kritis Siswa Madrasah Ibtidaiyah dalam Menyelesaikan Soal Hots Sejarah - Ismawa, Yayuk; Abidah, Mafruhatul; Lailiyah, Siti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2025)
This study aims to describe the critical thinking skills of elementary school students in solving problem-based questions. Higher Order Thinking Skills (HOTS) in the History subject of the Indonesian Proclamation material. This study employs a qualitative approach with a descriptive design, involving three subjects from grade VI at MI At-Tanwir Bojonegoro, who were selected using a purposive sampling technique based on categories of high, medium, and low critical thinking skills. Data were obtained through tests, interviews, and documentation, and then analyzed through the stages of data reduction, data presentation, and conclusion. The results of the study indicate that students with high critical thinking skills can fulfill all critical thinking indicators, such as interpretation, analysis, evaluation, and inference; students with medium abilities only fulfill some of the indicators; while students with low abilities have not demonstrated optimal critical thinking skills. These findings indicate that the application of HOTS questions in history learning in Madrasah Ibtidaiyah needs to be improved so that all students can develop critical thinking skills evenly.